A Companion to Archaeology. - Bintliff, John.
1 online resource (570 pages)
Keywords: A Companion to Archaeology features essays from 27 of the world's leading authorities on different types of archaeology that aim to define the field and describe what it means to be an archaeologist. Shows that contemporary archaeology is an astonishingly broad activity, with many contrasting specializations and ways of approaching the material record of past societies. Includes essays by experts in reading the past through art, linguistics, or the built environment, and by professionals who present the past through heritage management and museums. Introduces the reader to a range of archaeologists: those who devote themselves to the philosophy of archaeology, those who see archaeology as politics or anthropology, and those who contend that the essence of the discipline is a hard science.